PENGARUH LKS BERORIENTASI STRATEGI PEMBELAJARAN GENIUS DENGAN MENGINTEGRASIKAN NILAI KARAKTER TERHADAP HASIL BELAJAR FISIKA SISWA KELAS X SMA ADABIAH PADANG - Fauziah Fauziah; Asrizal Asrizal; Harman Amir (PILLAR OF PHYSICS EDUCATION, 2015)
The learning to make the students active, fun, and develop the character’s values need to be done. In reality, many students do not like Physics learning. The alternative solution that can be done is by applying  student worksheet which orientated to the genius learning strategy by integrating character’s values. Purpose of this research is to investigate the effect of student worksheet  that orientated to the genius learning strategy by integrating character’s values towards student’s achievement in  Physics learning in grade X of Senior High School Adabiah Padang. This research was a quasi experiment research. Randomized control group only design was the model of this research. The population of this research was all the students of grade X Senior High School Adabiah Padang who registered in the second semester in the year of 2013/2014. Sample of this research was gotten by applying purposive sampling, two classes was choosen that was X6 as experiment class and X5 as control class. The instrument was test for cognitive domain, observation sheet for affective domain, and worksheet’s assessment for psikomotor domain. The data analysis use compare mean test that was test t in the real level 0,05. The result of research showed that the mean of students in experiment class in each domain was higher than control class. It was the effect of using student worksheet that orientated tho the genius learning strategy by applying character’s values towards student’s achievement in learning Physics. It can be concluded that student worksheet which orientated to the genius learning strategy by applying character’s values towards student’s achievement in Physics learning was influential in teaching and learning process in grade X of SMA Adabiah Padang